Les verbes introducteurs de noms de sentiments en français et en allemand: étude comparative diachronique - Pierens, Matthieu (Neophilologica, 2018)
In this article we compared the introductory verbs of feelings in French (sentir, ressentir, éprouver) and in German ( fühlen, empfinden, (ver)spüren) across the time in order to bring to light the affinities between these verbs. To this end, we measured the principal collocations of these verbs and determined for each verb the most salient ones. This allowed us to determine affinities between French and German verbs according to the time. We also noticed the kind of feelings, which are more connected to feeling auxiliary verbs, notably pain, joy and pleasure, whereas emotion words such as anger and fear are less present.